PENERAPAN PENDEKATAN CONTEXTUAL TEACHING AND LEARNING (CTL) UNTUK MENINGKATKAN MOTIVASI DAN HASIL BELAJAR SISWA PADA MATERI VEKTOR DI KELAS X MIPA 5 SMA NEGERI 1 LOHBENER - Mulyana, Diki (Universitas Pekalongan, 2024)
This research is classroom action research conducted at SMA Negeri 1 Lohbener. The subjects in this research were class X MIPA 5 students, totaling 27 students. The instruments used in this study were observation sheets and questionnaires which aimed to measure students' learning motivation and formative tests given each cycle which aimed to measure the improvement of students' mathematics learning outcomes. The results of student learning motivation in cycle I experienced an increase from learning activities before the cycle with a value of 54.07 increased to 66.85 and the percentage of students who had high or very high motivation before the cycle was 29.63% of the total number of students then increased to 77.78% while student learning outcomes from the initial data before the cycle obtained an average value of 52.85 after the first cycle increased to 62.56 and the percentage of students who had completed learning was 25.93% of the total number of students before the cycle then increased In the first cycle, 55.56% of students had completed their studies or achieved the KKM score. In cycle II it gave better results than cycle I with an average score of students related to previous learning motivation of 66.85 to 84.10 while the percentage of students' learning motivation that was high or very high increased even more from cycle I of 77.78%. to 88.89% in cycle II and the average value of student learning outcomes from cycle I of 62.56 increased to 80.26 in cycle II and the percentage of students who had achieved mastery learning in cycle II increased by 77.78% compared to cycle I is 55.56% indicating that the use of the Contextual Teaching and Learning (CTL) approach in learning mathematics can increase student motivation and learning outcomes in vector material.